Webinar on Agriculture in the UNFCCC Negotiations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This two-hour webinar provided an overview of where and how agriculture is positioned in the UNFCCC climate negotiations, and it presents a series of resources for advocates and communicators to engage meaningfully in the UNFCCC process. It was aimed at climate change negotiators, their technical advisors and any agricultural organisation interested in food security and climate change. Speakers: Anette Engelund Friis, Head of Program Coordination, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Peter Iversen, former negotiator for Denmark James Kinyangi, CCAFS East Africa Michael Hoevel, Farming First The webinar was hosted by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and by the global agricultural coalition Farming First.